"Safer-by-design" synthesis of quantum dots in flow reactors. (October 2019) - Akdas, Tugce; Reiss, Peter
Abstract: After decades of research and commercialization efforts, colloidal semiconductor nanocrystals (quantum dots, QDs) are now on the verge of widespread application. Given the high demands of industrial production processes regarding process safety, cost efficiency and reproducibility of high quality products with high yield, continuous processes in flow reactors offer several advantages over the scale-up of a batch reaction. In this contribution, we discuss safety and operational issues for QD synthesis in micro- and millifluidic reactors using two case studies, i.e. synthesis of the two cadmium-free material systems, namely InP and CuInS2 . While current "Safe-by-Design" (SbD) discussions concerning nanomaterials mainly focus on material types and their toxicity, thus on the functionality of the final products, we will assess the production process as such, considering all chemicals involved in the various stages. In our contribution we discuss synthesis and downstream processing of core QDs and thereby show that flow synthesis of QDs can result in a "greener" and safer production routine.